DISTRIBUTION PATTERNS AND RELATIONSHIPS AMONG THE KEROS, GERA, AND YENIGUN CLASSIFICATION SYSTEMS IN THE MORPHOLOGICAL EVALUATION OF THE LATERAL LAMELLA OF THE CRIBRIFORM PLATE ON COMPUTED TOMOGRAPHY (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the distribution of risk levels according to Keros, Gera, and Yenigun classifications, and to analyze the relationships among these classifications as well as the correlation between the depth, angle, and length of the lateral lamella of the cribriform plate (LLCP) on computed tomography.Subjects and methods: A cross-sectional descriptive study was conducted on 149 patients (298 nasal sides) at Nhan Dan Gia Dinh Hospital from June 2024 to June 2025. The study variables included olfactory fossa depth (Keros), lateral lamella angle (Gera), and lateral lamella length (Yenigun). Distribution normality was assessed using the Shapiro-Wilk test. Because both nasal sides from the same patient were included, the primary analyses were performed using Generalized Estimating Equations (GEE) with patient ID as the clustering unit; Spearman correlation analyses based on the mean value of both sides per patient were additionally reported.Results: According to Keros classification, the medium-risk group (type II) predominated at 89.6%, while the high-risk group (type III) accounted for only 2.3%. In contrast, Gera classification identified a significantly higher proportion of high-risk cases (type III, angle < 45°) at 15.8%. The mean LLCP length was 11.83 ± 2.15 mm; Yenigun classification revealed that 7.0% of cases were in the high-risk group (type III > 15 mm). Statistical analysis showed that LLCP length varied independently of depth and angle. Notably, 95.2% of cases with a dangerous length (Yenigun type III) were concealed within the Keros low-to-medium risk groups.Conclusion: The Keros classification alone does not fully reflect the multidimensional anatomy of the anterior skull base. In this sample, LLCP length according to the Yenigun classification behaved as a morphological parameter independent of depth and angle. Considering depth, angle, and length together may provide a more comprehensive preoperative assessment of high-risk LLCP variants.
Keywords: Lateral lamella of cribriform plate, Keros classification, Gera classification, Yenigun classification, Computed tomography.